Functional role of striatal A2A, D2, and mGlu5 receptor interactions in regulating striatopallidal GABA neuronal transmission. Issue 2 (21st June 2016) - Beggiato, Sarah; Tomasini, Maria Cristina; Borelli, Andrea Celeste; Borroto‐Escuela, Dasiel Oscar; Fuxe, Kjell; Antonelli, Tiziana; Tanganelli, Sergio; Ferraro, Luca
Abstract: In this study, the functional role of individual striatal receptors for adenosine (A2AR), dopamine (D2R), and the metabotropic glutamate receptor mGlu5R in regulating rat basal ganglia activity was characterized in vivo using dual‐probe microdialysis in freely moving rats. In particular, intrastriatal perfusion with the D2R agonist quinpirole (10 μM, 60 min) decreased ipsilateral pallidal GABA and glutamate levels, whereas intrastriatal CGS21680 (A2AR agonist; 1 μM, 60 min) was ineffective on either pallidal GABA and glutamate levels or the quinpirole‐induced effects. Intrastriatal perfusion with the mGlu5R agonist (RS)‐2‐chloro‐5‐hydroxyphenylglycine (600 μM, 60 min), by itself ineffective on pallidal GABA and glutamate levels, partially counteracted the effects of quinpirole. When combined with CGS21680 (1 μM, 60 min), (RS)‐2‐chloro‐5‐hydroxyphenylglycine (CHPG; 600 μM, 60 min) fully counteracted the quinpirole (10 μM, 60 min)‐induced reduction in ipsilateral pallidal GABA and glutamate levels. These effects were fully counteracted by local perfusion with the mGlu5R antagonist MPEP (300 μM) or the A2AR antagonist ZM 241385 (100 nM). These results suggest that A2ARs and mGlu5Rs interact synergistically in modulating the D2R‐mediated control of striatopallidal GABA neurons. Using dual‐probe microdialysis, we characterized the functional role of striatal adenosine A2A receptor (A2AR), dopamine D2 receptor (D2R), and metabotropic glutamate receptor 5 (mGluR5) interactions in regulating rat basal ganglia activity. The results suggest the possible usefulness of using an A2AR antagonist and mGluR5 antagonist combination in the treatment of Parkinson's disease to increase the inhibitory D2 signaling on striatopallidal GABA neurons. Abstract : Using dual‐probe microdialysis, we characterized the functional role of striatal adenosine A2A receptor (A2AR), dopamine D2 receptor (D2R), and metabotropic glutamate receptor 5 (mGluR5) interactions in regulating rat basal ganglia activity. The results suggest the possible usefulness of using an A2AR antagonist and mGluR5 antagonist combination in the treatment of Parkinson's disease to increase the inhibitory D2 signaling on striatopallidal GABA neurons.